Faculty Senate, Agenda, September 16, 2010 - Faculty Senate, Valdosta State University (Valdosta, Ga: Valdosta State University Archives and Special Collections, 2010)
Valdosta State University. Faculty Senate, Agenda, September 16, 2010.
1 electronic document. Faculty Senate, Agenda, September 16, 2010. 21 pages.
Keywords: Valdosta State University. Faculty Senate; Corporation reports; Committees; Electronic records